Improved fallows in Eastern Zambia: history, farmer practice and impacts - Kwesiga, Freddie; Mafongoya, Paramu; Ajayi, Olu; Phiri, Donald; Katanga, Roza; Kuntashula, Elias; Place, Frank; Chirwa, Teddy; Franzel, Steven (International Food Policy Research Institute, 2005)
The decline in soil fertility in smallholder systems is a major factor inhibiting equitable development in much of sub-Saharan Africa. Some areas fallow in order to strength soil fertility for later planting, but as populations increase, demand follows and continuous cropping becomes the norm and there is a reduction in yields. This case study summarizes the development of improved tree fallows by researchers and farmers in eastern Zambia to help solve the problem of poor soil fertility. Many farmers are finding that by using improved fallows, they can substitute relatively small amounts of land and labor for cash, which they would need to buy mineral fertilizer. The study has three phases: the historical background (phase 1); an assessment of problems, description of the technology, and how it was developed (phase 2); and how the improved fallows practices were disseminated and spread (phase 3). This paper will describe each phase, the goals, and results.